Learning of higher education students through the itinerary in archaeological sites of Lima, Peru - Quijano Aranibar, Ivan Ernesto (2020)
The objective is to describe the level of learning of the students who participated through the itinerary in the reconstructed and consolidated archaeological site. The research approach is quantitative and the type descriptive. The non-experimental cross-sectional design has been chosen. The sample is non-probabilistic and consists of 20 students from the 3rd cycle of the Official Tourism Guide profession. The survey was applied through the PQ1 instrument. In addition, the IBM SPSS program was used for the analysis to obtain the central measures. The results show that students learn concepts in archeological sites through the itinerary, but these are based on static and dynamic levels 2 and 3 of learning.